Transforming activity of an oncoprotein-encoding circular RNA from human papillomavirus - Jiawei Zhao (Nature Portfolio, 2019)
The authors identify circular RNAs (circRNA) from human papillomavirus and show that circRNA-encoded E7 contributes to cancer cell growth in vitro and in tumor xenografts. Furthermore, circE7 is present in TCGA RNA-Seq data from HPV-positive cancers.